Studies on the black spot disease of citrus caused by Guignardia Citricarpa Kiely with particular reference to its epiphytology and control at Letaba - Le Roux, P.M. (University of Pretoria, 2013)
Thesis (DSc (Agriculture))--University of Pretoria, 1963.